Resolution of Islamic banking and takaful disputes in Indonesia and Malaysia : a comparative study - Abdul Rasyid (Ahmad Ibrahim Kulliyyah of Laws,International Islamic University Malaysia, 2013)
Islamic banking and takaful institutions in Indonesia and Malaysia have increased significantly both in numbers and number of services and products offered. A well-framed regulation is essential to support and develop their activities, more particularly in the sphere of disputes resolution. As shari'ah based institutions, their dispute resolution mechanism ought to be based on Islamic principles. This study examines the law of Islamic banking and takaful, and focuses on the dispute resolution mechanism in Indonesia and Malaysia. This study indentifies some Islamic dispute resolution mechanisms which might be appropriate for resolving disputes in Islamic banking and takaful. This research uses a qualitative approach; data were collected through various methods i.e. interviews, library and documentary searches. The collected data is then used in a comparative manner for analysing the issues and problems. The findings of this study show that laws governing Islamic banking and takaful in Malaysia are far ahead of Indonesia. In relation to resolution of disputes, the two countries have different approaches. In Indonesia, the Religious Courts have jurisdiction to settle Islamic banking and takaful disputes, while in Malaysia such disputes come under the jurisdiction of the Civil Court with its Mu'amalat Bench/Division. In addition to this court, alternative institutions such as BASYARNAS and KLRCA as well as FMB are also established in Indonesia and Malaysia respectively. This study suggests that for Indonesia, a special takaful law should be enacted in order to enhance its further development. The Religious Court and BASYARNAS must be the sole bodies for the resolution of Islamic banking and takaful disputes. Section 55(2) of Law No. 21 of 2008 concerning Islamic banking deserves to be repealed. Furthermore, to strengthen the role of BASYARNAS, a special regulatory law, based on Islamic law of arbitration, is needed and it should have a good infrastructure and professionally managed. FMB like body is also required to be established in Indonesia. In Malaysia, Islamic Banking Act and Takaful Act must be amended in order to bring institutional and procedural improvements of substantive nature. Following the example of Indonesian Religious Court, Mahkamah Shari'ah in Malaysia should also be given similar jurisdiction in settling Islamic banking and takaful disputes. To achieve this, Federal Constitution needs to be amended; alternatively, a special court for this purpose may be established. The setting up of a new Islamic Arbitration Centre for resolution of Islamic banking, takaful and finance is also suggested.